2013
DOI: 10.1111/mcn.12062
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of maternal fatty acids, micronutrients and homocysteine and their association with birth outcome

Abstract: Our earlier studies both in animals and in humans have indicated that micronutrients (folic acid, vitamin B12) and long-chain polyunsaturated fatty acids, especially docosahexaenoic acid (DHA), are interlinked in the one-carbon cycle, which plays an important role in fetal 'programming' of adult diseases. The present study examines the levels of maternal and cord plasma fatty acids, maternal folate, vitamin B12 and homocysteine in healthy mothers at various time points during pregnancy and also examine an asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 94 publications
5
21
0
1
Order By: Relevance
“…The fatty acid composition, relative to total fatty acids, was also largely modified during pregnancy. Similar findings for maternal fatty acids and their proportions in plasma and plasma phospholipids have been reported previously [39, 40]. DHA may be of particular importance to fetal brain and retinal development [38].…”
Section: Discussionsupporting
confidence: 84%
“…The fatty acid composition, relative to total fatty acids, was also largely modified during pregnancy. Similar findings for maternal fatty acids and their proportions in plasma and plasma phospholipids have been reported previously [39, 40]. DHA may be of particular importance to fetal brain and retinal development [38].…”
Section: Discussionsupporting
confidence: 84%
“…In relation to folate, some studies suggest a negative association between high maternal folate status and risk of low birth weight or small-for-gestational-age babies (van Uitert and SteegersTheunissen 2013). Meanwhile,vitamin B 12 deficiency has been associated with reduced birth weight (Wadhwani et al 2013), but no association with small-for-gestational-age babies has been found (Abraham et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…DHA supplementation reduces significantly the effects of prenatal stress and the perinatal mortality rate and also, increases the birth weight [46,48]. However for recurrent IUGR, it is not clear that a routine supplementation could improve fetal growth [50].…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study, Wadhwani et al reported a positive correlation between the maternal and umbilical cord plasma DHA concentrations and birth weight [48].…”
Section: Dha and Fetal Growthmentioning
confidence: 99%